Kemampuan Berpikir Analogis Siswa SMP dalam Menyelesaikan Masalah Matematika - Elgiyan, Naili Fauziyah; Wijayanti, Pradnyo (Universitas Negeri Surabaya, 2024)
This study aims to describe students' analogical thinking abilities in solving mathematical problems. The subjects of this study were one fieldindependent cognitive-style student and one junior high school student from class VII.. The instruments used are analogical thinking ability test, and interview . The results of this study show that students in the coding stage did not write down the information in the questions on their answer sheets, however, they were able to explain during interviews. In the conclusion stage, students use methods that they consider easy and have used these methods before. In the mapping stage, students can identify the relationship between the source problem and the target problem during the interview, which can be seen from the similarity of the information known and asked. In the application stage students get conclusions from the solution to the source problem and target problem.